Karakterisasi Tingkat Degradasi Superalloy Udimet 520 Pada Sudu Putar Turbin Pembangkit Listrik Tenaga Gas [Characteristic Degradation Level of Superalloy Udimet 520 of Rotating Blade of a Gas Turbine Power Plant] - Adnyana, Dewa Nyoman (Jurnal Metalurgi, 2018)
First stage rotating blades of a gas turbine power plant having design capacity of 130 MW have been in operation for more than 50.000 hours. The blade material was made of Udimet 520, a Ni- based superalloys. During its operation, the turbine blades may have been subjected to degradation due to several damage mechanisms such as thermal aging, creep, fatigue, corrosion and/or erosion. The aim of this examination was to determine the degree of degradation and the possibility of future service continuation of the turbine blades. A post-service first stage turbine blade was dismounted from the engine rotor and used for examination. Various laboratory examinations were performed including chemical analysis, metallographic examination, hardness testing and creep testing. Results of the examination obtained showed that the turbine blade material has not been experiencing some significant morphology change in microstructure due to thermal aging, either on the matrix austenite phase (g) and precipitate of gamma prime (g’) or on the carbide phase particles. In addition, the level of creep resistance of the turbine blade material was still higher than the minimum creep property of the Udimet 520. Furthermore, the degree of degradation due to corrosion and/or oxidation occurred on most of the blade exterior in general was considered low. Based on this condition, the first stage gas turbine blades were considered serviceable.